Altered corticospinal excitability of scapular muscles in individuals with shoulder impingement syndrome. - Ya-Chu Chung; Chao-Ying Chen; Chia-Ming Chang; Yin-Liang Lin; Kwong-Kum Liao; Hsiu-Chen Lin; Wen-Yin Chen; Yea-Ru Yang; Yi-Fen Shih (PLoS ONE, 2022)
The purpose of this study is to assess and compare corticospinal excitability in the upper and lower trapezius and serratus anterior muscles in participants with and without shoulder impingement syndrome (SIS). Fourteen participants with SIS, and 14 without SIS were recruited through convenient sampling in this study. Transcranial magnetic stimulation assessment of the scapular muscles was performed while the participants were holding their arm at 90 degrees scaption. The motor-evoked potential (MEP), active motor threshold (AMT), latency of MEP, cortical silent period (CSP), activated area and center of gravity (COG) of cortical mapping were compared between groups using the Mann-Whitney U tests. The SIS group demonstrated following significances, higher AMTs of the lower trapezius (SIS: 0.60 ± 0.06; Comparison: 0.54 ± 0.07, p = 0.028) and the serratus anterior (SIS: 0.59 ± 0.04; Comparison: 0.54 ± 0.06, p = 0.022), longer CSP of the lower trapezius (SIS: 62.23 ± 22.87 ms; Comparison: 45.22 ± 14.64 ms, p = 0.019), and posteriorly shifted COG in the upper trapezius (SIS: 1.88 ± 1.06; Comparison: 2.76 ± 1.55, p = 0.048) and the serratus anterior (SIS: 2.13 ± 1.02; Comparison: 3.12 ± 1.88, p = 0.043), than the control group. In conclusion, participants with SIS demonstrated different organization of the corticospinal system, including decreased excitability, increased inhibition, and shift in motor representation of the scapular muscles.